Instituto de Ciencia Animal: fifty years of experience in the evaluation of grasses with economical importance for animal husbandry - Herrera, Rafael S. (Cuban Journal of Agricultural Science, 2016)
This study deals with the main results of the evaluation of grasses in the Instituto de Ciencia Animal from 1965 to 2014. Evaluations took into consideration aspects related to species and varieties, soil preparation, sown and establishment, intercropping, rehabilitation, nutrition, production of biomass and seeds, plagues and their control, physiological aspects, chemical composition and quality. In addition, the study refers to the effect of these grasses on biomass production and some guidelines are suggested for further researches. Key words: grasses, evaluation